Edward Elgar’s Masque The Crown of India - Pucciarelli, Edvige (Il Tolomeo, 2018)
The music for The Crown of India was written by Edward Elgar in 1912 to accompany an ‘Imperial Masque’ with a libretto by Henry Hamilton. The impresario Sir Oswald Stoll had commissioned Elgar to compose the Masque music for the lavish celebration of the coronation of King George V as Emperor of India as part of a larger entertainment in the Coliseum Theatre in St. Martin’s Lane. The Masque was part of an ample music-hall programme, involving shows as different as mime, pantomime and music. Elgar’s ‘Imperial Masque’ was meant to be an assertion of the British Empire, bringing to the London stage the crucial political happenings behind all the pageantry of the Delhi Durbar for the crowning of George V as Emperor of India in December 1911. This event had marked the climax of the only royal tour of India undertaken by a reigning King-Emperor and had caused much public excitement in England. The Durbar ceremony itself was an adaptation of a court ritual of the Mogul Empire, an event where the ruling princes used to meet to discuss politics and legislative changes. To listen to works such as Elgar’s The Crown of India (Opus 66), it is necessary to acknowledge that at the beginning of the 20th century the British nation believed in the Empire and in its concept.